2003
DOI: 10.1038/sj.bmt.1704336
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of donor vaccination before hematopoietic cell transplantation and recipient vaccination both before and early after transplantation

Abstract: Summary:Allogeneic hematopoietic cell transplantation is followed by humoral immunodeficiency. We evaluated whether antibody levels can be improved by recipient vaccination on day À1 and 50 and whether the levels can be further improved by donor vaccination on day À20. A total of 85 patients were randomized or assigned to one of the following strategies of immunization with Streptococcus pneumoniae polysaccharides, Haemophilus influenzae polysaccharide-protein conjugate, tetanus toxoid (protein recall antigen)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
46
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 43 publications
1
46
1
Order By: Relevance
“…Moreover, pretransplant immunizations in both donor and recipient were found to potentiate Ab response post transplantation. 17 However, Storek et al 19 did not find that preHSCT donor and recipient vaccination resulted in detectable levels of antibodies. As HbsAg is a poorly immunogenic protein neoantigen, it is conceivable that repetitive donor vaccination may result in higher Ab titers and thus higher transfer of immunity.…”
Section: Varicellamentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, pretransplant immunizations in both donor and recipient were found to potentiate Ab response post transplantation. 17 However, Storek et al 19 did not find that preHSCT donor and recipient vaccination resulted in detectable levels of antibodies. As HbsAg is a poorly immunogenic protein neoantigen, it is conceivable that repetitive donor vaccination may result in higher Ab titers and thus higher transfer of immunity.…”
Section: Varicellamentioning
confidence: 99%
“…36 Donor immunization, however, can boost protective immunity for immunocompromised patients. 37 Storek et al 19 determined that Ab levels post transplant are improved by vaccinating the donor (20 days before transplant) as well as the recipient (1 day before transplant and 50 days post transplant) for H. influenzae. Parkkali et al 20 also confirmed that Hib Ab concentrations were significantly higher 12 months post transplant when the patient received a graft from a vaccinated donor.…”
Section: Varicellamentioning
confidence: 99%
See 2 more Smart Citations
“…3,[5][6][7][8][9] However, protection from reactivation depended on vigorous HBV immunity in the donor. 3,10 Therefore, donors should optimally receive more than one immunization, a rather high Ag dose and a highly immunogenic vaccine. As clearance from HBV infection is dependent on effective T-cell immunity, the protection of recipients can be estimated better if their HBV-specific cellular immune response is known.…”
mentioning
confidence: 99%